Prevalence Of Dysmenorrhea And Its Impact On Quality Of Life Among Health Care Workers - Prithika, Prithika; Revathy, T.G (Journal of Neonatal Surgery, 2025)
Background: Dysmenorrhea, characterized by painful menstruation, is prevalent among healthcare workers (HCWs), whose demanding job nature can worsen symptoms. Despite its frequency, menstrual health remains a less addressed concern in professional settings. Methods: A cross-sectional study involving 126 female HCWs aged 18–45 years was conducted using the DysmenQOL questionnaire. Data analysis utilized SPSS software, with chi-square tests examining the associations. Results: Dysmenorrhea prevalence was 81.7%, with 30.2% experiencing severe pain. About 67.5% reported reduced productivity, and 30.2% noted absenteeism. Emotional distress and sleep disturbances were common, yet only 10.3% sought medical help. Conclusion: Dysmenorrhea notably hampers work performance and mental well-being among HCWs. Workplace interventions are necessary to support menstrual health needs